Elemental mapping of plant leaves by MeV glass capillary microbeam PIXE - S. Wongke (2020)
© 2020 Elsevier B.V. MeV-ion microbeam using the capillary technique was home-developed based on the 1.7-MV tandem accelerator and beamline at Chiang Mai University. The system consisted of the capillary itself, a capillary holder, a holder swing mechanism, and a system support frame with a micrometer for vertical micro-adjustment. The glass capillaries had various sizes in a range of 10 – hundreds μm in the exit inner diameter. In this study, the capillary ion-microbeam was applied in elemental concentration distribution mapping of plant leaves using particle induced X-ray emission (PIXE) analysis. The interests were focused on difference in the elemental concentrations distributed between the leaf vein and lamina of local longan leaves which were sprayed by chemical fertilizer and pesticide and leaves of Peperomia pellucida, a herb, which was cultured by dissolved supplement solution of various nutrients. 1D and 2D maps of detected elements from the longan and herb leaves across vein and lamina were generated respectively, showing redistributions of the elements between vein and lamina due to the human activities. Details of the mapping results are reported and discussed.